2018
DOI: 10.1177/1078155218808866
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and evaluation of high-dose methotrexate administration guidelines

Abstract: Background High-dose methotrexate is used to treat a variety of malignancies. Methotrexate-associated supportive care and the threshold methotrexate level for the discontinuation of supportive care are not consistent among studies. We evaluated the implementation of high-dose methotrexate administration guidelines, which raised the standard threshold methotrexate level for the discontinuation of supportive care from <0.05 to <0.1 µmol. Methods A single-center, observational analysis of patients receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Another study also found similar patterns of low adherence to similar, more stringent monitoring of patients. 14 This practice pattern reflects a comfort level with earlier discharge that has been reinforced in recent clinical trials involving HD-MTX. 15 The patients in our pre-intervention cohort with levels .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Another study also found similar patterns of low adherence to similar, more stringent monitoring of patients. 14 This practice pattern reflects a comfort level with earlier discharge that has been reinforced in recent clinical trials involving HD-MTX. 15 The patients in our pre-intervention cohort with levels .…”
Section: Discussionmentioning
confidence: 86%
“…As suggested in previous studies, it may be safe to discharge patients home with an MTX level of 0.1 mmol/L without any supportive medications. 14,15 In our own preintervention cohort, 43% of patients were discharged when their MTX level was . 0.05 mmol/L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doses of 500 mg/m 2 or higher are regarded as high‐dose methotrexate (HDMTX) 2,3 . Moreover, HDMTX is the first‐line drug against various malignancies, including lymphomas, acute lymphoblastic leukaemia (ALL), osteosarcoma, and breast cancer 4 …”
Section: What Is Known and Objectivementioning
confidence: 99%
“…2,3 Moreover, HDMTX is the first-line drug against various malignancies, including lymphomas, acute lymphoblastic leukaemia (ALL), osteosarcoma, and breast cancer. 4 Although HDMTX is safely administered to the most patients, it can induce serious toxic responses, such as acute kidney injury (2%-12% of patients), gastrointestinal toxicity (10%-30% of patients), liver toxicity (25%-60% of patients), and neurotoxicity (up to 15% of patients). 1,5 Nephrotoxicity is one of the most significant toxicities of MTX.…”
Section: Introductionmentioning
confidence: 99%